RAPID ON-SITE EVALUATION AND MICRONUCLEUS SCORING IN BREAST LESIONS FINE NEEDLE ASPIRATION CYTOPATHOLOGY BY NEW IAC YOKOHAMA SYSTEM OF REPORTING - SAMRITI GOYAL; MOHANVIR KAUR; KANWARDEEP KAUR; ROMMEL SINGH MOHI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective of the study is to report all fine needle aspiration cytopathology (FNAC) cases of lump breast as per New Yokohama classification 2016, to highlight the importance of rapid onsite evaluation (ROSE) in breast cytology at the time of FNAC, and to assess the relationship between micronucleus (MN) scoring and various breast lesions in cytology. Methods: The study was conducted on 70 patients with breast lumps in the Department of Pathology in Government Medical College, Patiala, and comprised evaluation of ROSE and MN scoring in breast FNAC by the use of New Yokohama system of reporting. Results: On ROSE, 11 out of 70 patients were categorized under category I according to the Yokohama system of reporting and on the same sitting with repeat FNAC after performing the ROSE; nine cases were upgraded for cytological reporting and two remained in category I. According to as per the International Academy of Cytology (IAC) Yokohama system of reporting (2016) cases were categorized as category I – 2 (2.9%), category II – 46 (65.7%), category III – 7 (10.1%), category IV – 5 (7.1%), and category V – 10 (14.2%). In MN scoring, MN with the highest score of 14–17/1000 epithelial cells was in category V (malignant), and the lowest score was 0–1/1000 epithelial cells in category II (benign). Conclusion: ROSE is an easy, safe, and cost-effective method. IAC Yokohama system for reporting (2016) provides a comprehensive way of categorizing various breast lesions on FNAC with clinical correlation. MN score is a good biomarker in differentiating benign, atypical, and malignant breast lesions.